A case study of lithium exploration project in Barroso, Portugal: management and sustainability challenges in balancing costs and benefits - Pereira, Hugo (2024)
Portugal has the largest known reserves of lithium in Europe and the potential to be the largest producer of this mineral on the continent, a situation that has brought to public discussion the economic benefits and environmental costs of exploiting this mineral. In this context, this study explores the costs and benefits of overcoming management and sustainability challenges in lithium mining in Barroso, Portugal, which may contribute to shedding some light on the debate. The theoretical framework is within the scope of management accounting, particularly cost-benefit analysis and sustainability, focusing on lithium extraction. The methodology consists of a single case study, based on secondary data collected from documents and processed using content analysis. The results made it possible to identify costs and benefits in economic, social, and environmental terms and various analysis criteria, supporting the controversy in the balance of positions between the arguments of the project's economic promoters and the resistance of local social and environmental players.